Patent absurdity. - Frank, S.J (IEEE spectrum)
A growing chorus of critics in the popular press has chastised software developers, Web-application designers, and gene-patenting biotechnologists, among others, for securing patent rights that-it is said-subvert the system. The patent office has been cracking down. The most notable reforms affecting bad patents are statutory changes.